2021
DOI: 10.3390/molecules26195985
|View full text |Cite
|
Sign up to set email alerts
|

The Neuroprotective Role of Polydatin: Neuropharmacological Mechanisms, Molecular Targets, Therapeutic Potentials, and Clinical Perspective

Abstract: Neurodegenerative diseases (NDDs) are one of the leading causes of death and disability in humans. From a mechanistic perspective, the complexity of pathophysiological mechanisms contributes to NDDs. Therefore, there is an urgency to provide novel multi-target agents towards the simultaneous modulation of dysregulated pathways against NDDs. Besides, their lack of effectiveness and associated side effects have contributed to the lack of conventional therapies as suitable therapeutic agents. Prevailing reports h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 104 publications
0
15
0
Order By: Relevance
“…Owing to a delay between the experiments and this report, it was possible to find out which warm-blooded horses were already in use in sports and what their first sport results were. By 20 October 2021, roughly equal numbers of control ( 14) and knotweedfed (13) horses out of 26 in each category had already been registered for horse jumping and dressage competitions, and the control and knotweed-fed horses jumped over 104 and 109 cm high obstacles (in average; p = 0.3) and had been involved in 7 and 13 competitions (p = 0.15), respectively. These data are only of limited informative value as many other factors are involved, including socioeconomic ones.…”
Section: Sports Carrier Of the Experimental Horsesmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to a delay between the experiments and this report, it was possible to find out which warm-blooded horses were already in use in sports and what their first sport results were. By 20 October 2021, roughly equal numbers of control ( 14) and knotweedfed (13) horses out of 26 in each category had already been registered for horse jumping and dressage competitions, and the control and knotweed-fed horses jumped over 104 and 109 cm high obstacles (in average; p = 0.3) and had been involved in 7 and 13 competitions (p = 0.15), respectively. These data are only of limited informative value as many other factors are involved, including socioeconomic ones.…”
Section: Sports Carrier Of the Experimental Horsesmentioning
confidence: 99%
“…Immunity is regulated by its interfering with immune cell regulation, pro-inflammatory cytokines' synthesis and gene expression [8]. Similarly, piceid regulates lipid metabolism, helps treat cardiovascular diseases [9] and diabetic cardiomyopathy via its anti-inflammatory and anti-oxidative effects [10], preserves mitochondrial function in the central nervous system, offers a therapeutic option for Spinal cord ischemia/reperfusion injury [11], decreases the levels of reactive oxygen species in neurons from the ischemic cortex, ameliorates oxidative stress and mitochondria-dependent apoptosis [12], fights neurodegenerative diseases including Alzheimer's, Parkinson's, cognition/memory dysfunction, brain/spinal cord injuries, ischemic stroke and miscellaneous neuronal dysfunctionalities [13], promotes a radiosensitising effect on osteosarcoma cancer cells, reduces clonogenic survival of tumor cells and induces osteogenic differentiation, alone and in the presence of ionising therapy [14]. Emodin has recently garnered increased interest, with refs.…”
Section: Introductionmentioning
confidence: 99%
“…The therapeutic and protective effects of polydatin mainly originate from its anti-inflammatory, antioxidant, and anti-apoptotic activities [ 20 ]. Previous studies have shown a wide range of therapeutic effects of polydatin in the treatment of several pathological diseases such as cancer [ 21 ], cardiovascular diseases [ 22 ], diabetes [ 23 ], neurodegenerative diseases [ 24 ], hepatic/respiratory diseases [ 25 , 26 ], gastrointestinal diseases [ 27 ], infectious diseases [ 28 ], rheumatoid diseases [ 29 ], and skeletal/women disorders [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some evidence indicates that the chemical constituents of F. dentatoalata share a similar profile to those of F. multiflora. Emodin (21) and tetrahydroxystilbene-2-O-β-D-glucoside (26), for example, are two major compounds isolated from F. dentatoalata and F. multiflora which exhibit a wide range of neurobiological properties including neuroprotection and anti-neuroinflammation (Fakhri et al, 2021;Semwal et al, 2021). In adidtion, extracts from F. multiflora have been reported to show inhibitory activity against AChE (IC 50 : 9.11 μg/ml) and BuChE (IC 50 : 4.83 μg/ml) (Li et al, 2017).…”
Section: Introductionmentioning
confidence: 99%